Analysis of Silica Fume and Nano Silica Microstructure in High Performance Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
High performance concrete often has a  water-to-cement ratio that is lower than traditional concrete  in order to achieve the extended service life and appropriate  mechanical strength that are required by the design. Because  the presence of a large number of large pores or voids,  particularly when they are concentrated in a particular  region, can have an impact on the mechanical strength and  durability of concrete, reducing the quantity of such pores or  voids can help to increase the strength of the hydrated cement  paste that is used in this type of concrete. Because a  crystalline phase's strength increases with decreasing grain  size, the grain size of the materials used in the production of  concrete also has an effect on the characteristics of the  finished product. Extensive experimental work was carried  out to investigate the impact that different parameters had on  the results of mechanical, and durability tests carried out on  Nano Silicaand Silica Fume when they were subjected to  compression and the silica fume ranged from 0% ,1% ,2% to  3% and combination of nano silica and silica fume was  considered in which sililca fume values were considered  cconstant at 2% and nano silica varied from 0% ,0.5%, 1%,  to 1.5%. By this procedure an increase in the strength of the  concrete was found.
Keywords: Fine Aggregate; Water; Super Plasticizers; Silica Fume (SF); Nano Silica (NS)